PENGARUH DAYA TARIK WISATA, AKSESIBILITAS, FASILITAS, DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI UMBUL PONGGOK - Umi Nurchomariyah; Aditya Liliyan (Jurnal Pijar, 2023)
This studies changed into achieved with the purpose of examining the affect of elegance, accessibility, facility and word of mouth on vacationers' travelling decisions at Umbul Ponggok. Non-probability sampling became used as a sampling technique, the use of a purposive sampling method. a complete of 100 traffic to the Umbul Ponggok traveller appeal had been used as samples inside the observe. using primary facts and information series techniques by means of dispensing questionnaires, the usage of multiple linear regression as information analysis with SPSS model 26 software tools to technique information. The effects showed that vacationer enchantment did now not drastically affect the choice to go to vacationers at Umbul Ponggok. Accessibility has a substantial impact on the selection to visit vacationers at Umbul Ponggok. facility do no longer notably affect the decision to visit vacationers at Umbul Ponggok. word of mouth has a great effect on the decision to go to tourists at Umbul Ponggok. traveler attraction, accessibility, facility, and word of mouth together significantly have an effect on the decision to visit travelers at Umbul Ponggok